The monitoring and managing application of cloud computing based on Internet of Things. Issue 130 (July 2016) - Luo, Shiliang; Ren, Bin
Highlights: An efficient PSOSAA algorithm for the medical monitoring and managing application of the hospital information system is proposed. Introduce the information cloud system based on IoT for hospitals. The cloud computing and IoT technologies are used in medical area. Presents a model architecture for remote monitoring cloud platform of healthcare information. Abstract: Cloud computing and the Internet of Things are the two hot points in the Internet application field. The application of the two new technologies is in hot discussion and research, but quite less on the field of medical monitoring and managing application. Thus, in this paper, we study and analyze the application of cloud computing and the Internet of Things on the medical field. And we manage to make a combination of the two techniques in the medical monitoring and managing field. The model architecture for remote monitoring cloud platform of healthcare information (RMCPHI) was established firstly. Then the RMCPHI architecture was analyzed. Finally an efficient PSOSAA algorithm was proposed for the medical monitoring and managing application of cloud computing. Simulation results showed that our proposed scheme can improve the efficiency about 50%.